Empagliflozin induces apoptotic-signaling pathway in embryonic vasculature: In vivo and in silico approaches via chick’s yolk sac membrane model - Mosallanejad, Saeedeh; Mahmoodi, Mehdi; Tavakkoli, Hadi; Khosravi, Ahmad; Salarkia, Ehsan; Keyhani, Alireza; Dabiri, Shahriar; Gozashti, Mohammad Hossein; Pardakhty, Abbas; Khodabandehloo, Hadi; Pourghadamyari, Hossein (Frontiers in Pharmacology, 2022)
The present investigation was conducted to evaluate the vascular-toxicity of empagliflozin (EMP) in embryonic vasculature. Firstly, the vascular-toxicity of the drug as well as its interaction with apoptotic regulator proteins was predicted via in silico approach. In the next step, the apoptotic-signaling pathway in embryonic vasculature was evaluated using a chick’s YSM model. In silico simulation confirmed vascular-toxicity of EMP. There was also an accurate affinity between EMP, Bax and Bcl-2 (-7.9 kcal/mol). Molecular dynamics assay revealed complex stability in the human body conditions. Furthermore, EMP is suggested to alterBcl-2 more than BAX. Morphometric quantification of the vessels showed that the apoptotic activity of EMP in embryonic vasculature was related to a marked reduction in vessel area, vessel diameter and mean capillary area. Based on the qPCR and immunohistochemistry assays, enhanced expression level of BAX and reduced expression level of Bcl-2 confirmed apoptotic responses in the vessels of theYSM. We observed that induction of an apoptotic signal can cause the embryonic defect of the vascular system following EMP treatment. The acquired data also raised suspicions that alteration in apoptotic genes and proteins in the vasculature are two critical pathways in vascular-toxicity of EMP.